If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5x + 6 = 17 Reorder the terms: 6 + 0.5x = 17 Solving 6 + 0.5x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 0.5x = 17 + -6 Combine like terms: 6 + -6 = 0 0 + 0.5x = 17 + -6 0.5x = 17 + -6 Combine like terms: 17 + -6 = 11 0.5x = 11 Divide each side by '0.5'. x = 22 Simplifying x = 22
| -4(6x-7)=-24x-28 | | -12x-65=-7x | | 5-(2x+2)=-(-3x+5)-x | | 3(-2x+5)=9 | | 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 | | 7(-1x+5)=-7 | | x^2-2+3x+8=180 | | -8y=48-4y | | 7.1x+4.4-2x-8.7= | | -7(2x+4)=-70 | | [8x+5]=21 | | 72-10x=12 | | -6x+2=3x-79 | | [4x-8]=20 | | x+4=-20-x | | 6x-3=-7x-133 | | 4-3x+2x=-18+2 | | 6=16-13d | | -140=4x-6(-x+10) | | 5y=-2x-15 | | 10x^2-42x+44=0 | | 5x+13=35+7x | | -1-2x-6x=-65 |